Penerapan Pembelajaran Kooperatif Tipe Make A Match Materi Kruna Wilangan Pada Siswa Kelas 5 Sekolah Dasar No. 2 Kapal - Ni Putu Ayu Sri Laksmi; Gusti Nyoman Mastini; Kadek Dedy Herawan (Jayapangus Press, 2026)
This study aims to describe the effectiveness, challenges, and efforts of teachers in implementing the “Make a Match” cooperative learning model to improve students' understanding of multiplication tables at SD No. 2 Kapal. This qualitative study collected data through observation, interviews, and documentation. Data analysis is based on constructivist theory to examine the formation of students’ knowledge, as well as behaviorist theory to observe changes in learning behavior. The results of the study indicate that the implementation of the “Make a Match” model is effective in improving students’ understanding of multiplication tables. This improvement is specifically evident in students’ accuracy in identifying and matching word cards, as well as changes in learning behavior where students become more enthusiastic and confident in actively interacting. The challenges identified included some students’ slowness in absorbing the material and a lack of mastery of the basics of number sequences. To address these challenges, the teacher provided solutions in the form of more interactive visual teaching materials (pairing cards), increased the intensity of independent practice, and provided continuous individual guidance.